Apprécier les impacts sociaux des activités minières au Pérou : une étude de cas à l’échelle de la région Ancash - Nicolas Merveille (Cahiers des Amériques Latines)
In Peru, insufficient investment in research makes evaluation as well as prospective studies of the impacts generated by development projects difficult. For the last decade Defensoría del Pueblo noticed an increase in the number of social conflicts generated in large part, by a lack of knowledge about territorial dynamics by public authorities as well as private actors. Based on a case study in Ancash region in the central Peruvian Andes, the author proposes an original reading of the social impacts studies generated by the mining sector. The central idea of the paper is to combine the logic of measuring impacts indicators, with the need for assessment where some hidden variables (uncountable) play a fundamental role in assessing the effects and consequences induced by a megaproject.